2006
DOI: 10.1097/01.sap.0000235475.74372.67
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Success Rate of the Reversed-Flow Fasciocutaneous Island Sural Flap

Abstract: The reversed-flow fasciocutaneous island sural flap is presenting one of the best reconstructive options in the distal third of the leg, around the ankle and the heel up to the metatarsals. Although the surgical maneuver of this flap and many of its modifications have been well described in previous publications, the flap is unfortunately full of reported complications. In this work, we are presenting a 26-patient series of reversed-flow fasciocutaneous island flap cases in different age, sex, and etiologic gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
0
11
0
3
Order By: Relevance
“…Several studies have shown good results with the use of this flap [4][5][6][7][8][9][10][11][12][13] . Because several errors are common during the learning phase of this technique, describing these errors may improve the initial results and may support the continued use of this flap.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown good results with the use of this flap [4][5][6][7][8][9][10][11][12][13] . Because several errors are common during the learning phase of this technique, describing these errors may improve the initial results and may support the continued use of this flap.…”
Section: Introductionmentioning
confidence: 99%
“…The medial plantar artery flap is commonly used for small wounds of the heel pad and ankle (Cohen et al, 1999; Duman et al, 2002; Gu et al, 2017; Khai Luen & Wan Sulaiman, 2017; Oh, Moon, Cha, Koh, & Chung, 2011; Scaglioni, Rittirsch, & Giovanoli, 2018; Schwarz & Negrini, 2006; Siddiqi, Hafeez, Cheema, & Rashid, 2012). For slightly larger or proximal defects, the reverse sural flap or propeller flaps are options (Benito‐Ruiz, Yoon, Guisantes‐Pintos, Monner, & Serra‐Renom, 2004; El‐Shazly & Yassin, 2006; Lu, Chai, Wang, & Wen, 2014; Maffi, Knoetgen III, Turner, & Moran, 2005; Xu & Lai‐Jin, 2008). However, large, complex wounds, often the result of trauma, can limit the availability of these locoregional options and usually require the use of free flaps for coverage.…”
Section: Discussionmentioning
confidence: 99%
“…The distally based neuro-fasciocutaneous flaps with blood vessel perforators are advantageous (Cavadas, 1997;Costa-Ferreira et al, 2001;Almeida et al, 2002;El-Shazly and Yassin, 2006;Afifi et al, 2008;Saint-Cyr et al, 2009) for lower limb reconstruction, especially for soft-tissue defects on the ankle and joints; however, necrosis of a part or most of the flaps usually occurs because of disturbances in venous drainage. To resolve this problem, several researchers have adopted the "anastomosed superficial venous method" in distally based neuro-fasciocutaneous flaps and designed interesting ways of transferring the flap to prevent pedicle distortion and compression.…”
Section: Discussionmentioning
confidence: 99%